Hungarian Monitoring, 13 July 1988 . [Magyar rádiófigyelő], 1988. július 13 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Situation in Azerbaijan - Gorbachev in Szczecin - French statement on Romanian village reorganizations Domestic Affairs: - Károly Grósz's opinion on relations between government and parliament - Press conference at Gabčíkovo-Nagymaros dam site - Government establishes fund for those settling in Hungary Economy: - Hungary's Common Market chances Külpolitika: - Azerbajdzsáni helyzetkép - Gorbacsov Szczecinben - Francia jelentés a romániai településrendezésről Belpolitika: - Grósz Károly véleménye a kormány és a parlament kapcsolatáról - Sajtóértekezlet a bős-nagymarosi vízlépcső helyszínén - Letelepedési alapot hoz létre a kormány Gazdaság: - Magyarország Közös Piac-i lehetőségei